Social and conceptual issues in astrobiology - Smith, Kelly C. 1964-; Mariscal, Carlos (Oxford University Press, 2020)
To the humanities and beyond : exploring the broader questions in astrobiology / Kelly Smith and Carlos Mariscal -- Astrobiology and society : an overview / Steve Dick -- Hell is other planets : extraterrestrial life in the western theological imagination / Derek Malone-France -- Three lives and astrobiology / Lucas Mix -- Dimensions of life definitions / Emily Parke -- Meaning of the living state / Cole Mathis -- Life as it could be / Luis Campos -- Do extraordinary claims require extraordinary evidence? : the proper role of Sagan's dictum in astrobiology? / Sean McMahon -- Re-thinking conceptual intelligence and the astrobiology debate / Jason J. Howard -- What are extremophiles? : a philosophical perspective / Carlos Mariscal and Tyler Brunet -- Convergences in the ethics of space exploration / Brian Green -- Ethics and extra-terrestrials : what obligations will we have to extra-terrestrial life? what obligations will it have to us? / Adam Potthast -- METI or REGRETTI : ethics, risk and alien contact / Kelly C. Smith -- Earth, life, space : the social construction of the biosphere and the expansion of the concept into outer space / Linda Billings -- Myth-free space advocacy part IV : the myth of public support for astrobiology / Jim Schwartz -- Environmental law and space exploration / Christopher J. Newman
Includes index
Keywords: Astrobiologie; Ethik; Exobiology / Social aspects; Exobiology / Moral and ethical aspects; Exobiology / Philosophy; Life (Biology) / Philosophy; Aufsatzsammlung